AB0990 Rituximab in Chronic Autoimmune Rheumatic Diseases: Safety and Clinical Profile after 12 and 24 Months of Follow-Up. (15th July 2016) - Mata Martínez, C.; Garcia-Montoya, L.; Ovalles-Bonilla, J.G.; Nieto, J.C.; Lόpez-Longo, F.J.; Valor, L.; Serrano, B.; González, R.D.; Saenz, C.N.; Correyero, M.; Janta, I.; Martínez Barrio, J.; et al.
Abstract : Background: Rituximab (RTX) is a chimeric monoclonal anti-CD20 antibody. Several studies have proved its safety when used in different autoimmune chronic rheumatic diseases (ACRD). However, the real conditions of daily practice are not comparable to the ideal frame of a clinical trial. Objectives: The aim of this study is to describe the profile of safety of RTX in patients with ACRD 12 and 24 months after the administration of the first cycle. Methods: It is an observational retrospective study of patients diagnosed with ACRD who received treatment with RTX. Data were collected on demographic, clinical and biochemical profiles right before the first infusion, 12 and 24 months later. Other parameters were concomitant medication, prednisone dose, previous biologic treatment, accumulated RTX dose, infusion and anaphylactic reactions, infections, tumor relapses.Comparison was done using Wilcoxon non parametric test. Results: Data were collected from 50 patients that received RTX. 24 months after treatment no major cytopenias or hypogammaglobulinemia were found. Hepatic and lipid profile did not show any alterations and complement levels did not experiment relevant changes. The average dose of prednisone was reduced significantly 1 year after the treatment. A decline in levels of acute phase reactants and antibodies was observed. This effect was maintained in every parameter with the exception of the rheumatoid factor; which continued presenting a downwards trend after 24 months. Concerning the infections, 3 patients were hospitalised (because of severe infections): two of them suffered from pneumonia and the other one required a surgical intervention in order to replace an infected prosthetic knee. 14 mild infections were registered: 8 mucocutaneous, 2 gastrointestinal, 2 respiratory and 2 genitourinary. There were no cases of primoinfection, reactivation of hepatic viruses or mycobacteria. No tumoral relapses, new diagnosis of tumors or demyelinising diseases were observed. 5 patients experimented mild infusion reactions but none of them had an anaphylactic reaction or died. Conclusions: RTX has reduced the average maintenance dose of prednisone and also lowered the levels of serum immunoglobulins (including antibodies) without inducing hypogammaglobulinemia. It has proved to be a relatively safe treatment that does not cause hematic, hepatic toxicity or deep immunosuppresion after 12 and 24 months of follow up in patients with ACRD. Further studies are needed in order to evaluate long term safety of RTX. References: Becerra E et al; Long-term Safety of Rituximab in Patients With Rheumatoid Arthritis. Int J Clin Rheumatol. 2012;7(4):383–390. Disclosure of Interest: None declared